Aging Back Into the Closet: Community Planning for Older LGBTQ + Adults. (February 2022) - Turesky, Marisa
This article illuminates the unique experiences of older LGBTQ + adults in cities based on intersectionality theory. The main themes that emerged from the review of the literature were fear and isolation, service access, housing, and economic instability. The scholarship shows that many forms of marginalization influence this group's access to housing as well as health and care services for older LGBTQ + adults. I argue that planners must advocate for policies, trainings, and data collection to increase the social inclusion, economic security, health, housing and safety of older LGBTQ + adults.